Listening skill among socially disadvantaged students in relation to academic performance at higher education in West Bengal - Adak, Chayan; Panda, Bijoy Krishna (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2020)
Listening is the key to all effective communication. Good listening ability helps a person to make ideas, processing information, making pertinent comments, and ask relevant questions. This study aimed to understand existing listening skills among the socially disadvantaged students based on different demographic indicators and check whether listening skill and academic performance are somehow related when both the category of students are considered in higher education in West Bengal. Undergraduate freshman students of college and universities at West Bengal consisted of the population for the study where 225 students who regularly attended the course after successful completion of the higher secondary level selected as sample. Major findings revealed that the gender, stream, and medium of instruction has a significant contribution in a variation of listening skill (p<0.05); also, listening skill and academic performance is positively correlated with high statistical significance (p<0.01).